Comparison of Analysis Between Rectangular and Circular Overhead Water Tank - Latha M S (POLITEKNIK NEGERI JAKARTA, 2021)
Water tank is a container used for the storing of liquids and they are classified based on shape and location. The overhead tank is an important and it is very common public utility structure. The study predicts the analysis and design of the rectangular and circular overhead water tank using ETABS software. The water tank is modeled and analyzed by using dynamic analysis to resist lateral loads and design is made using working stress method manually. Dead load, live load, wind load and seismic loads are applied based on IS codes. The behavior of structure for the parameters like Story drift, displacement, stiffness, deflection, storey shear, base shear, area of steel and hoop tension for circular and rectangular water tank are studied and then comparison of the results is made between circular and rectangular overhead water tank. By this study we say that the circular water tank is suitable for larger capacity and rectangular is suitable for smaller capacity and it is economical for larger capacity.